2018
DOI: 10.1177/1591019918781778
|View full text |Cite
|
Sign up to set email alerts
|

Reversible cerebral vasoconstriction complicated with brain infarction immediately after carotid artery stenting

Abstract: Reversible cerebral vasoconstriction is a very rare complication after carotid artery stenting (CAS). It has been reported to occur more than several hours after CAS and to have a good clinical course. A 73-year-old man underwent CAS for a high-grade symptomatic stenosis of his left carotid artery. Immediately after CAS, he had consciousness disturbance and right hemiparesis. We first suspected hyperperfusion syndrome, but antihypertensive therapy exacerbated his symptoms. On repeated postoperative an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…It should be differentiated and treated appropriately. In previous reports, administration of calcium channel blockers, such as oral lomerizine hydrochloride 10 or intra-arterial verapamil, 8,11 was effective in the treatment of vasoconstriction after CAS. This study had some limitations.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…It should be differentiated and treated appropriately. In previous reports, administration of calcium channel blockers, such as oral lomerizine hydrochloride 10 or intra-arterial verapamil, 8,11 was effective in the treatment of vasoconstriction after CAS. This study had some limitations.…”
Section: Discussionmentioning
confidence: 97%
“…[1][2][3][4][5][6] In contrast, cerebral vasoconstriction cases after CAS have rarely been reported. [7][8][9][10][11][12] The purpose of this retrospective study is to present our observation on cerebral vasoconstriction in the ipsilateral anterior circulation during immediate poststenting angiography in patients with near-total occlusion (NTO) of the proximal ICA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that cerebral vasospasm occurs within 24 hours 2 , 3 , 5 and a few weeks after CAS. 6 , 7 The mechanism of vasospasm may differ between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…2,4,6 Vascular endothelial cell dysfunction and abnormal sympathetic nerve excitement cause cerebral vasospasm. [5][6][7] Watanabe et al reported that RCVS after CAS often occurs more than 2 weeks later. 7 However, our case occurred several hours after surgery.…”
Section: Observationsmentioning
confidence: 99%